Counterfactual thinking in moral judgment: an experimental study - Migliore, Simone; Curcio, Giuseppe; Mancini, Francesco; Cappa, Stefano F. (Frontiers in Psychology, 2014)
Counterfactual thinking is thinking about a past that did not happen. This is often the case in 'if only...' situations, where we wish something had or had not happened. To make a choice in a moral decision-making situation is particularly hard and, therefore, may be often associated with the imagination of a different outcome. The main aim of the present study is to investigate counterfactual thinking in the context of moral reasoning. We used a modified version of Greene’s moral dilemmas test, studying both the time needed to provide a counterfactual in the first and third person and the type of given response (in context-out of context) in a sample of 90 healthy subjects. We found a longer response time for personal vs. impersonal moral dilemmas. This effect was enhanced in the first person perspective, while in the elderly there was an overall slowing of response time. Out of context/omissive responses were more frequent in the case of personal moral dilemmas presented in the first person version, with females showing a marked increase in this kind of response. These findings suggest that gender and perspective have a critical role in counterfactual thinking in the context of moral reasoning, and may have implications for the understanding of gender-related inclinations as well as differences in moral judgement.